2021
DOI: 10.1101/2021.12.15.472778
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The African Swine Fever Isolate ASFV-Kenya-1033-IX is highly virulent and stable after growth in the wild boar cell line WSL

Abstract: In this study, we describe an African swine fever genotype IX virus (ASFV-Kenya-1033-IX), which was isolated from a domestic pig in Western Kenya during a reported outbreak, including efficiency of virus replication, in vivo virulence, and genome stability in pulmonary alveolar macrophages (PAM) and in a wild boar cell line (WSL). The ASFV-Kenya-1033-IX stock, which underwent multiple passages in WSL (more than 20), retained its ability to replicate in primary macrophages and it also retained the virulence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, WSL did not show efficient production of E70 or Armenia/07 [ 18 , 115 ]. More recently, two studies reported that WSL cells supported the growth of the virulent ASFV-Kenya1033-IX strain and of its derived mutant ASFV-KeΔA238L strain (generated by deletion of the gene A238L) [ 118 , 119 ]. ASFV-Kenya1033-IX reached levels in WSL similar to those obtained in PAMs when using an MOI of 1 [ 118 ].…”
Section: Porcine Continuous Cell Linesmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, WSL did not show efficient production of E70 or Armenia/07 [ 18 , 115 ]. More recently, two studies reported that WSL cells supported the growth of the virulent ASFV-Kenya1033-IX strain and of its derived mutant ASFV-KeΔA238L strain (generated by deletion of the gene A238L) [ 118 , 119 ]. ASFV-Kenya1033-IX reached levels in WSL similar to those obtained in PAMs when using an MOI of 1 [ 118 ].…”
Section: Porcine Continuous Cell Linesmentioning
confidence: 99%
“…At the genomic level, Hemmil and colleagues observed only a few single nucleotide differences between ASFV-Kenya1033-IX grown in macrophage or passaged in WSL [ 118 ], and Abkallo and colleagues confirmed the stability of the virus in this cell line; no SNPs, deletions, or rearrangement were observed in ASFV-Kenya1033-IX and its derived mutant ASFV-KeΔA238L replicating in WSL [ 119 ]. In addition, both NH/P68 and ASFV-Kenya1033-IX passaged several times in WSL were still able to infect and replicate in both primary macrophages and pigs; all of these studies are paving the way for the development of an ASFV-LAV in the future [ 18 , 118 ].…”
Section: Porcine Continuous Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations